Utility of the interferon-gamma release assay for latent tuberculosis infection screening among indian health-care workers - Sunita Girish; Aarti Kinikar; Geeta Pardesh; Sangita Shelke; Anita Basavaraj; Ajay Chandanwale; Dileep Kadam; Samir Josh; Gauri Dhumal; Nilima Lokhande; Andrea Deluca; Nikhil Gupte; et al. (Wolters Kluwer Medknow Publications, 2021)
Background: The utility of interferon-gamma release assays (IGRAs) for latent tuberculosis infection (LTBI) screening among health-care workers (HCWs) in low- and middle-income countries (LMICs) remains unclear. Methods: This was a prospective cohort study among HCW trainees undergoing annual LTBI screening via tuberculin skin test (TST) and QuantiFERON® TB Gold Test-in-tube (QFT-GIT) in Pune, India. TST induration ≥ 10 mm and QFT-GIT ≥ 0.35 IU/ml were considered positive. Test concordance was evaluated at entry among the entire cohort and at 1 year among baseline TST-negative participants with follow-up testing. Overall test agreement was evaluated at both timepoints using the kappa statistic: fair (k < 0.40), good (0.41 ≥ k ≤0.60), or strong (k > 0.60). Results: Of 200 participants, prevalent LTBI was detected in 42 (21%) via TST and 45 (23%) via QFT-GIT; QFT-GIT was positive in 27/42 (64%) TST-positive and 18/158 (11%) TST-negative trainees. Annual TST conversion was 28% (40/142) and included 11 trainees with baseline TST-/IGRA+; QFT-GIT was positive in 17/40 (43%) TST-positive and 5/102 (5%) TST-negative trainees. Overall test concordance was 84% (k = 0.52; 95% confidence interval [CI]: 0.38-0.66) and 80% (k = 0.44; 95% CI: 0.29-0.59) at baseline and 12 months, respectively. Conclusions: We observed good overall agreement between TST and QFT-GIT, and QFT-GIT detected additional LTBI cases among TST-negative trainees with possible early detection of LTBI conversion. Overall, our results support the use of IGRA for annual LTBI screening among HCWs in a high burden LMIC setting.